Corporate Responsibility for the Crime of Terrorism Financing in Indonesia - Yossri Mantaw Sihombing; Yasmirah Mandasari Saragih; Mhd. Azhali Siregar; Abdur Rahman Sirait; Teguh Hidayat Siregar (International Journal of Law and Society, 2024)
Criminal act Terrorism is a form of crime or serious violation human rights at the international level because it seriously endangers security and peace world . T he crime of terrorism which occurred in the territory of the unitary state of the Republic of Indonesia has resulted in loss of property and property and causing fear in society at large, thus having an impact on social life, economics, politics and international relations . One of the main factors supporting acts of terrorism is the existence of funding, meaning that terrorist activities will not take place if there are no funds. Therefore, it is very important to eradicate criminal acts of terrorist financing in order to minimize the occurrence of acts of terrorism. The research method used is normative legal research, namely legal research that uses secondary data by using a statutory approach and a conceptual approach . The data processing and analysis technique used in this research is a qualitative technique using deductive logic in order to draw conclusions from the problem formulation that has been described. The aim of this research is to determine the methods of collecting funds carried out by corporations for terrorism financing in Indonesia and to determine corporate responsibility for criminal acts of terrorism financing in Indonesia.